Life According to Popular Children's Films - Hare, Sara; Benham, Mariah (Advances in Social Sciences Research Journal, 2021)
This content analysis uses data gathered from the 150 top-grossing children’s animated films from 1990 to 2020 (based on North American theater sales) to examine the gender disparities and stereotypes in children’s media. The study shows that female characters are underrepresented in lead roles (14%), main gangs (28.1%), and speaking roles (27.2%). The central female characters are portrayed stereotypically. When female characters appear, they are more likely to be portrayed in a romantic and family relationship than male characters. However, films with a greater percentage of women writers are correlated with more speaking roles for female characters. The impact of media on children’s development is indisputable due to the way technology has become ingrained in day-to-day life. The lack of representation of female characters reinforces the stereotypical portrayals that negatively affect the self-esteem of girls and train boys to expect an androcentric world. The skewed and stereotypical portrayal of female characters fails to accurately represent the diversity of other parts of the world. While many of these films are produced in the West, they are widely distributed and consumed all over the world.